Signal-to-noise, spatial resolution and information capacity of coherent diffraction imaging. (2018) - Gureyev, Timur E.; Kozlov, Alexander; Nesterets, Yakov I.; Paganin, David M.; Martin, Andrew V.; Quineya, Harry M.
No abstract available